Relationship of parameters of the impulsivity – reflexivity cognitive style with propensity to Internet addiction in high school students - E. P. Grigoriev; A. S. Galchenko; L. V. Poskotinova (Бюллетень сибирской медицины)
Aim. To study the relationship between parameters of the impulsivity – reflexivity cognitive style and the level of Internet addiction among high school students.Materials and methods. 154 students from general education institutions aged 16–17 years were diagnosed using the J. Kagan’s reflection – impulsivity test and the Chen Internet Addiction Scale. The one-way analysis of variance was used, followed by post-hoc pairwise comparisons using the Tukey’s test.Results. An inverse relationship between the level of Internet addiction and decision latency in a multiple-choice situation and a direct relationship between the level of Internet addiction and the number of errors in the J. Kagan’s reflection – impulsivity test were revealed.Conclusion. High school students with propensity to Internet addiction tend to have the impulsive cognitive style, while students without such a tendency – the reflective style. In cognitive activity, the impulsive cognitive style is generally less productive than the reflexive one. The impulsive cognitive style is similar to the so-called clip thinking, which allows to consider the relationship between Internet addiction and this phenomenon through the prism of cognitive and style features.